Berberine stimulates lysosomal AMPK independent of PEN2 and maintains cellular AMPK activity through inhibiting the dephosphorylation regulator UHRF1 - Ren, Gang; Ding, Yu-Wei; Wang, Lu-Lu; Jiang, Jian-Dong (Frontiers in Pharmacology, 2023)
Aim: AMPK is the key regulatory kinase mediating the effect of berberine (BBR) and metformin on metabolic improvement. The present study investigated the mechanism of BBR on AMPK activation at low doses, which was different from that of metformin. Methods: Lysosomes were isolated, and AMPK activity assay was performed. PEN2, AXIN1 and UHRF1 were investigated through gain/loss of function approaches, including overexpression, RNA interfering and CRISPR/Cas9-mediated gene knockout. Immunoprecipitation was utilized for detecting the interaction of UHRF1 and AMPKα1 after BBR treatment. Results: BBR activated lysosomal AMPK, but weaker than metformin. AXIN1 mediated BBR’s effect on lysosomal AMPK activation, while PEN2 did not. BBR, but not metformin, decreased UHRF1 expression by promoting its degradation. BBR reduced the interaction between UHRF1 and AMPKα1. And overexpression of UHRF1 abolished the effect of BBR on AMPK activation. Conclusion: BBR activated lysosomal AMPK as dependent on AXIN1, but not PEN2. BBR maintained cellular AMPK activity by reducing UHRF1 expression and its interaction with AMPKα1. The mode of action of BBR was different from that of metformin on AMPK activation.